Implikasi Trip's Terhadap Konvensi Keanekaragaman Hayati - Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2005)
The Protection of Intellectual Property Rights regulated on TRIP'S raises negative and positive impacts to the Biological Diversity Convention. The Protection of Intellectual Property Rights appliedto Invention on the biotechnology encouragespeople to invent a new variety of plant, on the other hand, the Protection of Intellectual Property Rights causes disadvantages to the developing countries such as patentedof traditional knowledge owned by Indigenous people of a State or patented of a certain kind-of plant.Furthermore. TRIP'S also raises negative Impact to the objective of the Biological Diversity Convention, such as the decrease of biological diversity.